POSTMENOPAUSAL VIRILIZATION: THE TELLTALE SIGN OF A RARE OVARIAN TUMOR - Tan , Mayple Leou Jiun; Lee, Xe Hui (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Postmenopausal virilization describes the occurrence of male secondary characteristics in a postmenopausal woman, contributed by excess androgen that originating from either the ovaries or adrenal glands. Relative androgen excess could be due to menopausal transition or polycystic ovarian syndrome. However, with virilizing symptoms, further investigation is warranted to look for ovarian hyperthecosis or androgen-secreting ovarian or adrenal tumors. Sertoli-Leydig cell tumors are considered significantly rare, accounting for less than 1% of all primary ovarian tumors. Diagnosis of these rare tumors can be challenging. CASE We report a case of a 68-year-old woman of Indian ethnicity who first presented to us at 60 years old in 2017 with postmenopausal hirsutism. Treatment with co-cyprindiol (Diane-35) for a year and spironolactone did not alleviate her symptoms but instead worsened them with other virilizing symptoms such as deepening of voice, breast atrophy and androgenic alopecia. Testosterone levels were persistently elevated [43.757 nmol/L (December 2016) – 48 nmol/L (July 2017) - >52 nmol/L (October 2019)]. Computed tomography imaging done in 2020 showed an enlarged right ovary. She was referred to Gynecology and was given one dose of Leuprorelin (Lucrin) on 11/7/2020, with the intention to assess ovarian suppression; however, elevated testosterone levels persisted at >52 nmol/L. The patient eventually underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy (TAHBSO) in May 2021 and histopathology revealed a right ovarian Sertoli-Leydig cell tumor. Post-operation testosterone levels showed rapid reduction to normal at 0.3 nmol/L and remained normal at <0.1 nmol/L in September 2021. CONCLUSION This case emphasizes the importance of thorough evaluation in women with postmenopausal virilization, which can be the only sign of rare ovarian tumors. Additionally, this condition can be distressing to patients and affect their quality of life, especially social interactions. The delay in her diagnosis and surgery highlights the need to increase awareness of this condition among clinicians.